Mind Matters: A Critical Look at Malaysia's Postnatal Depression Policy for Women's Mental Health - Aishah Siddiqah Alimuddin; Nuur Asyikin Mohd Shukor; Shean Yih Soh; Rosnadia Suainbon; Asma Assa’edah Mahmud; Farah Deena Abdul Samad; Nurazah Ismail; Muna Hamiza Asiff (Mary Ann Liebert Inc., 2024)
Indexed by WOS/Scopus